Late metastasis of renal cell carcinoma cloaked in a non-healing foot ulcer: A very rare presentation - G. Harika; G. Bou Kheir (Urology Case Reports, 2021)
A 67-year-old male who underwent right radical nephrectomy 15 years prior to current diagnosis for pT2bN0M0 ccRCC presented with an isolated purulent ulcer on left foot. Data was collected from records, radiological scans and histological reviews. The non-healing ulcer did not respond to antibiotic therapy and surgical debridement. Biopsy and histology confirmed a ccRCC metastasis. Late cutaneous ulcer is an aggressive and rare presentation of ccRCC metastasis. Awareness of a non-healing skin ulcer on a background history of ccRCC is important in order to avoid misdiagnosis and mistreatment.